Teachers Challenges and Strategies of Using Microsoft Office 365 in Teaching Online Classroom during Pandemic - Diva Rizkana Hasanah; Dian Novita Dewi (TEKNOSASTIK, 2022)
This study aims to explain (1) the teachers challenges in using Microsoft Office 365 in online teaching classroom during the pandemic, and (2) the strategies used by teachers to solve their problems in teaching online classes during the pandemic. The participants of this research were the teachers of SD Mustajabah. A qualitative method was employed in this research and using interviews via WhatsApp as a data collection technique. The findings showed that teachers had the challenges such as (1) operating the Microsoft Office 365 during online learning, and (2) discovering the suitable materials to gain students' attention during the online class. The strategies used by teachers to solve their problems in teaching online classes such as (1) maintaining the communication with parents of students, (2) developing thoughtful and creative materials, (3) making new agreements regarding online class.